Synthesis and characterization of silicon carbide nanotube via microwave assisted method - Voo, Tony Chung Sung author (School of Nano Electronic Engineering, Universiti Malaysia Perlis, 2018)
This study focused on the feasibility of synthesis of SiCNTs by using microwave heating and the effect of processing parameters on the formation of SiCNTs. The objectives of thisstudy are ; to investigate the effect of molar ratio of SiO2:MWCNTs, heating temperature and heating durationon the formation of SiCNTs by microwave heating in terms of morphology, compositions, optical and thermal properties ; to investigate the effect of types of CNTs (MWCNTs and SWCNTs) on the formation of SiCNTs by microwave heating in terms of morphology, compositions, optical and thermal properties.